On the Governance of Women’s Rights in Taliban Afghanistan: A Public Good No More - Graham, Molly (Stance: an international undergraduate philosophy journal, 2023)
Since the Taliban resumed political power in Afghanistan in August 2021, their total application of strict Sharia Law has demanded global attention. This paper theorizes that, in pursuit of social order, the Taliban has enacted a civil religion to justify their complete reversion of women’s rights as a public good. I examine Afghanistan's social contact through the political philosophies of Thomas Hobbes and Jean-Jacques Rousseau and suggest why the intended social order has not materialized. In conclusion, I depict the erosion of women's rights as a matter of structural injustice and incite critical reflexivity towards our responsibility for global justice.